2020
DOI: 10.1002/sctm.20-0199
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cell-derived lung organoids in an ex vivo model of the congenital diaphragmatic hernia fetal lung

Abstract: Three-dimensional lung organoids (LOs) derived from pluripotent stem cells have the potential to enhance our understanding of disease mechanisms and to enable novel therapeutic approaches in neonates with pulmonary disorders. We established a reproducible ex vivo model of lung development using transgene-free human induced pluripotent stem cells generated from fetuses and infants with Bochdalek congenital diaphragmatic hernia (CDH), a polygenic disorder associated with fetal lung compression and pulmonary hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 95 publications
(223 reference statements)
3
24
1
Order By: Relevance
“…Previous studies reported the hPSC-derived lung organoids that represent different respiratory compartments and utilized these models for gaining a deeper understanding of cell-to-cell communications during early lung development and pathogenesis of alveolar diseases, such as Hermanski-Pudlak syndrome and Bochdalek congenital diaphragmatic hernia [11][12][13][14][15]25 . However, the application of hPSC-derived lung organoids that recapitulate the complexity and function of the native lung tissue for disease modeling and drug screening has remained challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the hPSC-derived lung organoids that represent different respiratory compartments and utilized these models for gaining a deeper understanding of cell-to-cell communications during early lung development and pathogenesis of alveolar diseases, such as Hermanski-Pudlak syndrome and Bochdalek congenital diaphragmatic hernia [11][12][13][14][15]25 . However, the application of hPSC-derived lung organoids that recapitulate the complexity and function of the native lung tissue for disease modeling and drug screening has remained challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Because pulmonary defects and alterations in the space of the chest cavity occurred prior to diaphragm closure and may even be the cause of a diaphragm defect ( 32 ), it is interesting to study the space in the chest cavity in other CDH models and potentially in human fetuses to serve as an early predictor for CDH. To mimic limited chest space and compression, lung organoids have been subjected to mechanical pressure, which altered their development ( 44 ). These results show that extrinsic factors play a significant role in CDH pathogenesis and the influence of limited space and compression should be studied further, since Wt1 knock-out lungs still had the capacity to develop normally ex vivo , which is promising for potential treatment strategies ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition or genetic manipulation that causes CDH resulted in reduced in vitro proliferation in PPF-derived fibroblasts ( 43 ). Also, lung organoids were recently derived from induced pluripotent stem cells (iPSC) from fetuses and infants with CDH and showed reduced generation of lung progenitor cells and impaired epithelial- and mesenchymal differentiation ( 44 ). Recently, it was shown that organoid cultures can be obtained with a low input material from clinical samples, like tracheal aspirates from preterm newborns, and this method could also be used to grow organoids from CDH patients without the need of in vitro differentiation from iPSCs ( 45 ).…”
Section: Cellular Models In Cdh Researchmentioning
confidence: 99%
“…A summary of recent studies [7,8,10,15,[19][20][21][22][23][24][25][26][27][28] in which human airway organoids were employed for disease modeling and drug testing is presented in Table 1 [7,8,10,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Since 2017, several reports of disease modeling and drug testing using human airway organoids have been published.…”
Section: Disease Modeling and Drug Screening Research Using Human Airway Organoidsmentioning
confidence: 99%
“…Models of infections with viruses, Cryptosporidium parvum oocysts, and sporozoites were created by direct addition into organoid culture wells [7,8,10,20,22,26,27]. Furthermore, cystic fibrosis, a genetic disease that affects the respiratory system, and pneumonia, which also has a major genetic component, have been studied via human organoid models [8,20,23,25,28]. For the cystic fibrosis model, cystic fibrosis cell lines were obtained; they were made into patient-specific induced pluripotent stem cells (iPSCs) lines, and CFTR gene editing was performed to compare the results [8,25].…”
Section: Disease Modeling and Drug Screening Research Using Human Airway Organoidsmentioning
confidence: 99%